PENGARUH VOLUME KENDARAAN TERHADAP KERUSAKAN JALAN PADA RUAS JALAN LEMBAR SELATAN - KEBUN AYU: Influence Of Vehicle Volume On Road Damage On The South Lembar Road Section - Kebun Ayu - Muda, I Nengah Aditya Dwi Ade Sanjaya; Wijaya, Lalu Hardi; Aminullah, Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
Roads are an important factor in ensuring continued comfort and safety for all motorists, based on observations in the field, the condition of the South South Sheet crossing road to Kebun Ayu, which is approximately 5.7 km long, needs to be taken seriously and handled seriously by the government because the condition of the road has many potholes and bumps. The aim of this research is to determine the effect of vehicle volume on the level of road damage, and to determine the relationship between vehicle volume and the level of road damage on flexible pavement. This research is a case study research on the South South Sheet crossing road to Kebun Ayu. The data used in this research is secondary data such as road data and traffic volume data obtained from the West Lombok Regency Bina Marga service. Meanwhile, primary data obtained directly in the field includes vehicle volume data recorded during peak hours. The results of field data analysis showed that the road damage value (Nr) on the Southsheet – Kebun Ayu road was obtained with an average value (Nr) of 68.2; The traffic volume at peak hours based on passenger car units (pcu/hour) on the Kebun Ayu – South Sheet road is 560 pcu/hour, and in the South South Sheet - Kebun Ayu direction it is 546 pcu/hour. The equation for traffic volume analysis related to the value of road damage and time is Y = 0,025 X1 + 0,101 X2 + 25,74  with the magnitude of R2 or the correlation between variable x and variable y of 0.86 or 86%